2009
DOI: 10.1002/gps.2299
|View full text |Cite
|
Sign up to set email alerts
|

What do Korean American immigrants know about Alzheimer's disease (AD)? The impact of acculturation and exposure to the disease on AD knowledge

Abstract: There is a need to expand AD education efforts among Korean American immigrants because the views of stigmatization and normalization of AD combined with certain Asian cultural norms can be barriers to early recognition and intervention. Our study suggests knowledge areas of concentration in AD education and a segment of the population that AD education should target. Further research on symptom knowledge by the disease stages and causal beliefs is needed to better understand the existing views about AD in Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 42 publications
4
82
0
11
Order By: Relevance
“…Dementia is often considered as a part of the normal aging process rather than a disease, and this view is particularly prominent among Asian Americans (Ayalon & Areán, 2004;Braun, Takamura, Forman, Sasaki, & Meininger,1995;Braun, Takamura, & Mougeot, 1996;Dilworth-Anderson & Gibson, 2002;Lee, Lee, & Diwan, 2010;Yeo, Tran, Hikoyeda, & Hinton, 2001), even among younger and better educated Asian Americans (Jones, Chow, & Gatz, 2006). Stigma and shame attached to dementia are especially stronger among Asian American than African American, Latino, and/or White older adults (Ayalon & Areán, 2004;Hinton, Guo, Hillygus, & Levkoff, 2000;Jones et al 2006;Lee et al, 2010;Mahoney, Cloutterbuck, Neary, & Zhan, 2005;Yeo et al, 2001). Normalization and stigmatization have been suggested as significant barriers to timely medical and social interventions (Ayalon & Areán, 2004; Downloaded by [Stony Brook University] Guo, Levy, Hinton, Weitzman, & Levkoff, 2000;Hinton et al, 2000;Jones et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Dementia is often considered as a part of the normal aging process rather than a disease, and this view is particularly prominent among Asian Americans (Ayalon & Areán, 2004;Braun, Takamura, Forman, Sasaki, & Meininger,1995;Braun, Takamura, & Mougeot, 1996;Dilworth-Anderson & Gibson, 2002;Lee, Lee, & Diwan, 2010;Yeo, Tran, Hikoyeda, & Hinton, 2001), even among younger and better educated Asian Americans (Jones, Chow, & Gatz, 2006). Stigma and shame attached to dementia are especially stronger among Asian American than African American, Latino, and/or White older adults (Ayalon & Areán, 2004;Hinton, Guo, Hillygus, & Levkoff, 2000;Jones et al 2006;Lee et al, 2010;Mahoney, Cloutterbuck, Neary, & Zhan, 2005;Yeo et al, 2001). Normalization and stigmatization have been suggested as significant barriers to timely medical and social interventions (Ayalon & Areán, 2004; Downloaded by [Stony Brook University] Guo, Levy, Hinton, Weitzman, & Levkoff, 2000;Hinton et al, 2000;Jones et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, our sample of older ESL Chinese immigrant women may not be generalizable to other ESL (including Chinese) groups with respect to either less education or recent immigration. It has been shown that the longer immigrants are resident in the "host" country, the more likely they are to assimilate mainstream cultural beliefs about disease causation [33,34]. Second, women were specifically asked during the interview about the causes of colon cancer; however, they were not probed about what prevented colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority have a stigmatized view of AD as a form of insanity, and do not recognize that forgetfulness in old age can be an initial sign of the disease (Lee et al, 2010). With these misconceptions, KA immigrant families are likely to overlook the early symptoms of dementia, and they may seek medical help only after the disease is at an advanced stage.…”
Section: Lack Of Knowledge and Inaccurate Beliefs About Admentioning
confidence: 98%
“…However, KA immigrants still have incorrect beliefs and a significant lack of knowledge about the disease (Lee, Lee, & Diwan, 2010).…”
Section: Lack Of Knowledge and Inaccurate Beliefs About Admentioning
confidence: 99%